Shortcomings In The Legal System On Limited Partnership In Vietnam - Cuong, Ngo Huy; Hung, Nguyen Vinh; Duy, Nguyen Dang (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Currently, Vietnamese law does not clearly distinguish between limited partnerships and general partnerships. Limited partnerships are still merged with general partnerships in several provisions of the 2020 Enterprise Law. In other words, Vietnam's enterprise legal system still presents many shortcomings related to the recognition and regulation of limited partnerships. However, studies on the compatibility between limited partnerships and the current Vietnamese commercial environment reveal that limited partnerships offer several advantages over general partnerships. Moreover, limited partnerships also possess distinctive benefits that are not found in other company types such as joint-stock companies or limited liability companies in Vietnam. Despite these advantages, limited partnerships have not received sufficient attention from lawmakers and investors. To address this gap, this article employs a qualitative research method with a literature and legal approach. It systematically analyzes legal documents, academic articles, and comparative studies of corporate law to explore the suitability of limited partnerships in Vietnam's commercial setting. Through this method, the article identifies the existing legal deficiencies, evaluates the practical relevance of limited partnerships, and proposes specific legal reforms and policy recommendations to promote their development. The findings aim to contribute to the ongoing discourse on enterprise law reform and enhance the diversity of business organization forms in Vietnam.